Answer:
![1(4)/(13)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/9nnnbeiv31zsc3pwjim4mw5mpvmh1bbvt2.png)
Explanation:
-3 (3x-3) = 4/5 (5x-10)
-----------------------------
This also equals to:
-3*(3x-3)=4/5*(5x-10)
-----------------------------
Start by opening the parentheses:
-3*(3x-3)=4/5*(5x-10)
Then use distributive property:
(-3*3x) + (-3*-3)= (4/5*5x) + (4/5*-10)
Simplify the equation:
(-3*3x) + (-3*-3)= (4/5*5x) + (4/5*-10)
-9x+9= 4x-8
+8 +8
-9x+17= 4x
+9x +9x
17= 13x
÷13 ÷13
17/13=x
17/13=
![1(4)/(13)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/9nnnbeiv31zsc3pwjim4mw5mpvmh1bbvt2.png)
-----------------------------
:) Have a good day!